THE NYADRAN TRADITION AND THE CHANGING ROLES OF JAVANESE TRANSMIGRANT WOMEN - Ramona, Elza; Muhsin, Imam (Khazanah: Jurnal Studi Islam dan Humaniora, 2024)
The Nyadran tradition has become an important part of the life of the Javanese transmigrant community. Through the Nyadran tradition, Javanese transmigrant women can establish relationships, both with God, with nature as their place of residence, and with fellow human beings. By using the concept of Gender as an analytical tool, this study aims to see how the Nyadran tradition rituals are carried out by the Javanese transmigrant community, and to see how the role of women is in the Nyadran tradition rituals. In this study used a qualitative-descriptive method with unstructured interview data collection techniques. Data collection was also carried out by tracing the literature on the Nyadran tradition, both in the form of books and journal articles. The results showed that the Nyadran tradition was carried out by the Javanese transmigrant community every year, 10 days before the arrival of the month of Ramadan. This tradition is carried out by visiting the tombs or visiting the graves of the ancestors, tahlilan, listening to religious lectures, and feasting or eating together. In practice, women's roles are still found in the domestic sphere. Starting from providing various types of flowers and water, bringing yasin books and mats, and preparing ubarampe or various types of cakes and rice along with side dishes. Women are also subordinated by not being given the opportunity to deliver religious lectures. Through the delivery of religious interpretations, women are also subordinated and become a form of stereotype and shows that the patriarchal culture is still strong in the Javanese transmigrant community.